Czechia: Health System Review - Bryndová, Lucie; Šlegerová, Lenka; Votápková, Jana; Hrobon, Pavel; Shuftan, Nathan; Spranger, Anne (Health systems in transition, 2023)
This analysis of the Czech health system reviews developments in governance, organization, financing and delivery of care, health reforms and health system performance. Czechs have enjoyed a statutory health insurance system with a high level of financial protection, a broad benefits package and universal membership for over 30 years. The central level of the state, mostly represented through the Ministry of Health and its subordinated bodies, takes on the various roles of legislator, steward and even owner of various providers of care, while also making insurance contributions for the sizeable part of the population classified as economically inactive. Health insurance funds are responsible for contracting sufficient care provision for their members. The Czech health system has traditionally derived a majority of its financing from public sources, which stood at 81.5% of current health expenditure in 2019, as the latest available year of reference, with the rest coming from private sources. While health spending in Czechia is below the European Union (EU) average, the densities of acute care beds and primary care physicians are above respective EU averages. Ageing and a lack of qualified staff (for example, nurses in hospitals) are already putting pressure on the Czech health workforce, a bottleneck further exposed by the COVID-19 pandemic. Additionally, Czechia has embarked on a reform process to modernize and centralize specialized tertiary care and psychiatric care. Patients enjoy free choice of primary and specialized outpatient providers, though there are signs that accessibility is limited in some regions and for some specialties. Overall, health outcomes in terms of life expectancy, mortality and survival rates of stroke and cancer have improved in recent years, though these improvements have been slower in Czechia than in other countries. However, life expectancy dropped considerably due to heightened mortality resulting from the COVID-19 pandemic in 2020 and 2021. There remains considerable room for improvement in strengthening disease prevention and health promotion, particularly for dietary habits and health literacy. Various efforts to advance evidence-based interventions in the health system, such as the initiation of health care quality monitoring and health system performance assessment, will assist in further analysing Czechia's health outcomes.
Keywords: reforma zdravotní péče; Health Expenditures; výdaje na zdravotnictví; Insurance, Health; pandemie; kvalita zdravotní péče; Health Policy; COVID-19; zdravotní pojištění; Pandemics; Health Care Reform; Humans; Česká republika; lidé; zdravotní politika; Quality of Health Care; Czech Republic